The effect of electronic medical record and service time on outpatient satisfaction - Dimas Kurnia Hidayat; Nurdin Nurdin; Rahmat Suyanto; Nanda Ghaffar Dwi Putra (Jurnal Manajemen dan Pemasaran Jasa, 2022)
Patient satisfaction is the first indicator of a hospital's standards and is a measure of service quality. From the survey we found Some problems that could reduce the level of patient satisfaction including registration does not have a barcode; the system is not fully integrated; aspects of medical records are not yet complete and technologically, electronic medical records are not developed perfectly. simple. The purpose of this study was to determine and analyze the description of the performance of the Electronic Medical Record (EMR), service time, and patient satisfaction, as well as analyze the effect of electronic medical records and service time simultaneously and partially on patient satisfaction in the out-patient section of Al-Ihsan Hospital Bandung. This research used quantitative research methods. The population is outpatients of Al-Ihsan Hospital, Bandung Regency, with a total of 30,425 patients per month. A simple random sampling technique was used in this research, while a questionnaire was selected as the data collection tool utilized in this study. Description tabulation methods analysis and Multiple linear regression analysis were used to thoroughly analyze the data. The results showed that the performance of electronic medical had a significant effect on theservice time in the outpatient section of RSUD Al Ihsan Bandung as a whole was rated effective and quick, and also in patient satisfaction. high. Hypothesis testing showed that there is a simultaneous and partial effect of electronic medical record performance and service time on patient satisfaction. Satisfaction will be realized if the customer or patient gets a fast, smooth, and unimpeded EMR system as well as optimal service time and fast and precise service time.